2015
DOI: 10.1021/acs.chemmater.5b00842
|View full text |Cite
|
Sign up to set email alerts
|

Series of Liquid Separation System Made of Homogeneous Copolymer Films with Controlled Surface Wettability

Abstract: Exquisite surface wettability control of separation system surface is required to achieve separation of liquids with low surface tension difference. Here, we demonstrate a series of surface-energy-controlled homogeneous copolymer films to control the surface wettability of polyester fabric, utilizing a vapor-phase process, termed as initiated chemical vapor deposition (iCVD). The homogeneous copolymer films consist of a hydrophobic polymer, poly (2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane), pV4D4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…The chemical vapor-phase process is another frequently reported method that enables the deposition of functional polymers onto various vulnerable substrates, including polyester fabric. [42] Importantly, the wetting behavior of liquids on the as-prepared fabrics was well consistent with the calculated interfacial energy value, presenting a precise control of surface wettability.…”
Section: Two-component Polymerssupporting
confidence: 73%
See 1 more Smart Citation
“…The chemical vapor-phase process is another frequently reported method that enables the deposition of functional polymers onto various vulnerable substrates, including polyester fabric. [42] Importantly, the wetting behavior of liquids on the as-prepared fabrics was well consistent with the calculated interfacial energy value, presenting a precise control of surface wettability.…”
Section: Two-component Polymerssupporting
confidence: 73%
“…In 2015, Kwak and colleagues utilized the iCVD process to prepare different copolymer fi lms made from the blending of a hydrophobic monomer, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (V4D4), and a hydrophilic monomer, 4-vinylpyridine (4VP). [ 42 ] In Figure 7 c, it was clearly observed that polymer-coated polyester fabrics showed an excellent capacity to control wetting behaviors of various liquids, e.g., water, glycerol, EG and olive oil that are in close surface tension to each other. Moreover, the as-prepared fabric separated these four liquids sequentially with a high selectivity, just by choosing a copolymer-coated fabric with appropriate surface energy (Figure 7 d).…”
Section: Sample Separation and Purificationmentioning
confidence: 94%
“…In particular, the core functionalities of monomers are fully retained during the deposition process. [28] In addition, by exploiting the advantage of the homogeneous mixing between arbitrary monomer species, [29,30] we also recently reported the synthesis of high-k copolymer dielectric from 2-cyanoethyl acrylate (CEA) with highly polar cyanide functionality and di(ethylene glycol) divinyl ether (DEGDVE) as a cross-linker. [24][25][26][27] Among the different iCVD-based polymer films, low-k (≈2.…”
Section: Doi: 101002/aelm201800688mentioning
confidence: 99%
“…PDVB and two poly(divinylbenzene‐ r ‐methacrylic acid) (PDVB‐ r ‐PMAA) copolymers were selected as the cross‐linked neutral layer and top coat materials. The surface composition (i.e., the DVB:MAA ratio in PDVB‐ r ‐PMAA) was controlled systematically by simply tuning the relative input flow ratio of DVB and MAA, and the film thickness was adjusted by the deposition time (detailed characterization in Table S1 and Figures S2 and S3, Supporting Information), making iCVD a powerful tool for developing an ultrathin neutral layer that requires homogeneous surface composition …”
mentioning
confidence: 99%